'Doc, can I fly to Australia?' A case report and review of delirium following long-haul flight. (February 2017) - McCabe, Thomas
Summary: Air travel is now a common feature of most of our elderly population's lives. There is little by way of warnings, rules or recommendations for our patients with psychiatric diagnoses, in particular dementia, who intend to travel by plane, in contrast to other specialties. In this article I highlight an adverse outcome of long-haul air travel as a result of delirium and resulting accelerated decline in overall cognitive function. I review literature related to the topic and suggest ways to minimise precipitating factors for stressors prior to and during flights. This article suggests that more thought should be given to the title question.